2018
DOI: 10.3389/fpls.2018.01228
|View full text |Cite
|
Sign up to set email alerts
|

BABA-Primed Histone Modifications in Potato for Intergenerational Resistance to Phytophthora infestans

Abstract: In this paper we analyzed β-aminobutyric acid (BABA)-primed epigenetic adjustment of potato cv. “Sarpo Mira” to Phytophthora infestans. The first stress-free generation of the potato genotype obtained from BABA-primed parent plants via tubers and seeds showed pronounced resistance to the pathogen, which was tuned with the transcriptional memory of SA-responsive genes. During the early priming phase before the triggering stress, we found robust bistable deposition of histone marks (H3K4me2 and H3K27me3) on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 80 publications
(106 reference statements)
2
35
0
Order By: Relevance
“…However, CCF and BABA treatments did not induce SA production, although they up-regulated the PR genes ( PR1 for BABA and CCF and PR2 for BABA only) that are SA pathway activation markers. These results confirm and expand previous reports [ 30 , 31 , 54 , 55 ], who demonstrated that CCF and BABA can activate the SA signaling pathway. Saubeau et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, CCF and BABA treatments did not induce SA production, although they up-regulated the PR genes ( PR1 for BABA and CCF and PR2 for BABA only) that are SA pathway activation markers. These results confirm and expand previous reports [ 30 , 31 , 54 , 55 ], who demonstrated that CCF and BABA can activate the SA signaling pathway. Saubeau et al .…”
Section: Discussionsupporting
confidence: 93%
“…[ 30 ] observed on potato a SA peak 12h after CCF treatment and the PR s genes were up-regulated from 24h-48h [ 31 ]. In the same way, on soybeans, 15 SA pathway genes are up-regulated 24h after BABA treatment [ 55 ]. By contrast, the Ulva extract induced the OPR3 gene and increased OPDA and JA production, as also observed by Jaulneau et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that the non-protein amino acid, namely β-aminobutyric acid (BABA), effectively mediates the conditioning of induced plant defense mechanisms leading to enhanced protection against various pathogens (Cohen et al, 2016). Although BABA pre-treatment or other stimuli may prime a plant against future stress (Floryszak-Wieczorek et al, 2015; Meller et al, 2018), there is also evidence that such stress memory establishment is a relatively rare event or priming is reset during the period of stress recovery (Zimmerli et al, 2000; Pecinka et al, 2009; Crisp et al, 2016; Hilker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The H3K4me2 epigenetic mark was identified in high numbers on the gene body of StWRKY1, PR1 , and PR2 concomitant with transcript downregulation detected in leaves of primed potato and its descendants before the triggering stress. Moreover, our previous study revealed that the primed state in potato was associated with the transcriptional memory to post-infection histone acetyltransferase (HAT) activation in the next generation after the challenge inoculation with P. infestans (Meller et al, 2018). In the present study, with the same experimental design as mentioned above, we investigated how DNA methylation and demethylation in potato contribute to BABA-primed changes associated with transcriptional memory to improve resistance against the virulent P. infestans MP977.…”
Section: Introductionmentioning
confidence: 99%
“…In potato, priming with BABA increased resistance to the oomycete pathogen Phytophthora infestans , the causal agent of late blight disease [ 71 ]. The first unstressed generation of the BABA-primed parent plants showed increased resistance to the P. infestans , probably due to the upregulation of SA-responsive genes.…”
Section: Epigenetic Responses To Stressful Factorsmentioning
confidence: 99%